ANALISIS KEBAHASAAN K.H. AHMAD MUWAFIQ DALAM CERAMAH “REKONSILIASI PERAN PEMUDA DALAM BINGKAI KEBANGSAAN” - Marianita Anjarsari (STKIP PGRI Jombang, 2020)
In general, language as a community communication tool is usually used by certain groups of people who belong to the language community. Language communities are those who feel that they own and use the same language. Community members have different backgrounds and social status. For example there are differences in employment, education, and so on. As a result of differences that occur variations in language. This study aims to describe the form of 1) variations of idiolects, 2) variations of dialects, 3) variations of registers, and, 3) variations of code switching made by K.H. Ahmad Muwafid in the Reconciliation Lecture on the Role of Youth in the National Frame at Karangdurin Islamic Boarding School, Madura. This research uses descriptive qualitative method, with data collection techniques in the form of SBLC techniques and note taking techniques. The data validity technique uses data triangulation. The results showed that K.H. Ahmad Muwafiq uses idiolastic variations, namely 1) the use of regional languages such as Javanese or Madurese, and Betawi, and there is a mixture of Arabic, 2) the use of Javanese words, 3) the use of hyperbole and metonemical language styles, and 4) pronunciation of existing words in Arabic. K.H. Ahmad Muwafiq uses East Javanese, Madurese, or Sundanese dialects. K.H. Ahmad Muwafiq uses the list of priests. K.H. Ahmad Muwafiq did the code switching. The benefits of this research are expected to be insight into various languages in the world of preaching.